(untitled) - Charles G Nauert (Cambridge, New York, 1995)
The book traces the humanist "movement" from its origines in medieval culture and through the appropriation of classical Antiquity, and connects it to the social and political environments in which it subsequently developed
Keywords: europe - history - renaissance, 1450-1600,humanism